Drive-Thru Service System for Motor Vehicle Tax Collection and Its Impact on Taxpayers - Amalia, Mia; Lestari, Adinda Dwi; Zahra, Dina Islami; Syahidah, Fatiya; Khairunnisa, Halyza; Jenab, Siti (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Taxes are mandatory contributions by the state to individuals or legal entities, which are coercive and regulated by laws and regulations. This contribution is not accompanied by direct rewards, but is used for state needs in order to advance the welfare of the people as a whole.Purposes of the Research: This study aims to analyze how the Drive-Thru service system affects the level of taxpayer compliance in paying motor vehicle taxes and also to find out how community satisfaction in services and taxpayer compliance by using the Drive-Thru system for tax collection.Methods of the Research: This research method uses a qualitative method with a normative juridical approach, by using relevant laws and regulations, as well as legal doctrines related to the legal issues being studied.Results of the Research: The results showed that the implementation of the Samsat Drive-Thru system has a positive and significant effect on taxpayer compliance, where ease of access and time efficiency are key factors that increase public interest in paying vehicle taxes. Apart from that, this study also found that the importance of taxpayer awareness, tax knowledge, and tax sanctions as part of influencing compliance in paying taxes. Thus, innovations in tax service systems such as Samsat Drive-Thru can contribute to increased local revenue through better tax compliance.